Association of Metabolic Risk Factors With Cartilage Degradation Assessed by T2 Relaxation Time at the Knee: Data From the Osteoarthritis Initiative1. Issue 12 (December 2013) - Jungmann, P. M.; Kraus, M. S.; Alizai, H.; Nardo, L.; Baum, T.; Nevitt, M. C.; McCulloch, C. E.; Joseph, G. B.; Lynch, J. A.; Link, T. M.
<x xml:space="preserve">Abstract</x> Objective To evaluate the association of metabolic risk factors with severity and 2‐year progression of early degenerative cartilage changes at the knee, measured with T2 relaxation times in middle‐aged subjects from the Osteoarthritis Initiative. Methods Cartilage segmentation and T2 map generation were performed in knee 3T magnetic resonance images from 403 subjects ages 45–60 years without radiographic osteoarthritis (OA). The influence of risk factors on baseline T2 and longitudinal progression of T2 was analyzed using linear regression, adjusting for age, sex, and other OA risk factors. Results Four metabolic risk factors, i.e., high abdominal circumference (P < 0.001), hypertension (P = 0.041), high fat consumption (P = 0.023), and self‐reported diabetes mellitus (P = 0.010), were individually associated with higher baseline T2. When the 4 metabolic risk factors were considered in a multivariate regression model, higher T2 remained significantly associated with abdominal circumference (P < 0.001) and diabetes mellitus (P = 0.026), and there was a trend for high fat consumption (P = 0.096). For the individual risk factors, only diabetes mellitus remained associated with higher baseline T2 after adjustment for body mass index (BMI). After adjustment for BMI, baseline T2 increased in a dose‐response manner with the number of metabolic risk factors present (P = 0.032 for linear trend), and subjects with ≥3 metabolic factors (versus <3) had significantly higher baseline T2 (mean difference 1.2 msec [95% confidence interval 0.3, 2.1]; P = 0.011). Metabolic risk factors were not significantly associated with increases in T2 during followup. Conclusion Metabolic risk factors are associated with higher T2, suggesting that increased cartilage degeneration may be caused by modifiable metabolic disorders.